Implementation of Human Resource Management Strategy at PT Angkasa Pura Indonesia - Agung Abdu Kalam; Eci Meysindi Fitri; Ilham Pratama Putra; Leony Vihandini; Satriadi Satriadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the implementation of Human Resource Management (HR) strategies at PT Angkasa Pura Indonesia, Tanjungpinang branch, and their impact on employee performance. The method used is qualitative research with data collection techniques using semi-structured interviews and documentation to explore employee experiences. Data analysis used descriptive analysis. The results of the study indicate that the HR management strategy implemented has succeeded in improving employee performance, both in administration and operations, which ultimately has an impact on the effectiveness of the company. Development and training programs such as technical skills training, managerial leadership training, career development training, innovation and problem-solving training, and new technology training implemented by PT Angkasa Pura Indonesia, Tanjungpinang branch, have proven to significantly improve employee performance.